1979
DOI: 10.1080/03036758.1979.10419416
|View full text |Cite
|
Sign up to set email alerts
|

Northland Allochthon

Abstract: The name Northland Allochthon is proposed for the thick and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(81 citation statements)
references
References 46 publications
(36 reference statements)
4
77
0
Order By: Relevance
“…It lagged 2-3 m.y. behind a similar cycle of subsidence and eversion in northern Northland, during which giant nappes of Cretaceous-Paleogene rocks (Northland Allochthon) were emplaced from the northeast (Ballance & Spörli 1979;Hayward et al 1989;Hayward 1993), burying older in situ Miocene sedimentary rocks.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…It lagged 2-3 m.y. behind a similar cycle of subsidence and eversion in northern Northland, during which giant nappes of Cretaceous-Paleogene rocks (Northland Allochthon) were emplaced from the northeast (Ballance & Spörli 1979;Hayward et al 1989;Hayward 1993), burying older in situ Miocene sedimentary rocks.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…1), and these are thought to be at or near its southern limit (Isaac et al 1994). However, it has been suggested that the allochthon extends beneath the Waitemata Group, as far south as Waikato Fault (Ballance & Sporli 1979), and that it may be present beneath the Waitemata Group in the Karaka 1 well, drilled on the Manukau Lowlands (Hayward 19821 (Fig. 1).…”
Section: Southern Extent Of the Northland Allochthonmentioning
confidence: 99%
“…The North Cape, Whangarei and Auckland 4-mile geological maps of the 1960s showed isolated, small areas of 'Onerahi Formation' emplaced over younger strata, but these maps and the East Cape sheet predated recognition of the widespread overthrust and imbricated nature of much of the Cretaceous and Palaeogene strata (Stoneley 1968;Ballance & Sporli 1979). The Kaitaia, Whangarei, Auckland and Raukumara QMAPs portray the extents of the Northland and East Coast allochthons and show that, on a regional scale, they can be resolved into mappable sub-units based on age and lithology ( colour of allochthonous units provides a unifying identity.…”
Section: The Northland and East Coast Allochthonsmentioning
confidence: 99%